Power System Sensitivity Matrix Estimation by Multivariable Least Squares Considering Mitigating Data Saturation - Liang, Yingqi; Zhang, Junbo; Srinivasan, Dipti (IECON 2020 The 46th Annual Conference of the IEEE Industrial Electronics Society, 2020)
To online estimate the power system sensitivity matrix considering mitigating data saturation, a series of multivariable least-squares (MLS) algorithms are proposed and compared, including the ordinary MLS (OMLS), the weighted MLS (WMLS), the memory-limited OMLS (ML-ORMLS), the memory-limited WRMLS (ML-WRMLS), and the memory-fading ML-WRMLS (MF-ML-WRMLS). Considering enhancing computational efficiency and accuracy by mitigating data saturation, the last three of them are specifically derived for sensitivity matrix online estimation using online-measured data. The effectiveness of the presented algorithms is verified and compared in the Nordic 32 system for voltage sensitivity matrix estimation. The results illustrate the prime algorithm in practice.